Impediments of Supply Chain Management Application in Readymade Garments Industry of Bangladesh - Chowdhury, AHM Yeaseen; Islam, Nazrul; Alam, Md Zahedul (Journal of Business and Social Sciences Research, 2019)
There is a paramount importance of the Readymade Garments (RMG) industry of Bangladesh as it is the highest contributor in earning foreign exchange for the country. But the industry is facing stiff competition from other RMG producing countries including China, India, and Sri Lanka of the world. Hence, competitiveness especially at the manufacturing level became important for this industry. An efficient Supply Chain Management can increase the competitiveness and the satisfaction of the customers. Nowadays, SCM plays an integral part of a firm’s success as it allows firms to quickly deliver products to the end-user for a low cost. Hence, RMG companies have very limited options other than implementing SCM as a strategy in order to remain competitive. This study intends to identify the impediments in applying sound SCM in the RMG industry. A mixed research method with a questionnaire survey has been employed for determining the impediments objectively. Use of descriptive analysis and Kendall Coefficient of Concordance have been made for ranking the challenges. This study found workplace safety, unavailability of raw materials and political instability are the major impediments for SCM applications in the RMG industry of Bangladesh.